2022
DOI: 10.25289/ml.2022.11.2.97
|View full text |Cite
|
Sign up to set email alerts
|

Fractional laser and low-level light combination therapy in patients with recalcitrant alopecia areata

Abstract: Background and ObjectivesThe current treatment options for alopecia areata (AA) typically aim to suppress inflammatory T-cell responses. Patients vary in their response to these treatments, and some do not respond to one or more types of therapy. Herein, we report the outcomes of combination therapy, employing fractional laser treatment and low-level light therapy (LLLT), with a focus on patients with recalcitrant AA. Materials and MethodsLLLT (HEALITE II ® ; Lutronic, Goyang, Republic of Korea) and fractional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Using a medical device with a high output of infrared radiation (600-1,600 nm), 46.7% of patients with patchy AA showed hair regrowth in the treated areas 1.6 months sooner than in the untreated areas [26]. Recently, Yoo et al [27] demonstrated that the combination therapy of LLLT and fractional laser treatment may be a promising approach to treat recalcitrant AA. Considering the excimer laser's expense and potential adverse side effects,…”
Section: Alopecia Areatamentioning
confidence: 99%
“…Using a medical device with a high output of infrared radiation (600-1,600 nm), 46.7% of patients with patchy AA showed hair regrowth in the treated areas 1.6 months sooner than in the untreated areas [26]. Recently, Yoo et al [27] demonstrated that the combination therapy of LLLT and fractional laser treatment may be a promising approach to treat recalcitrant AA. Considering the excimer laser's expense and potential adverse side effects,…”
Section: Alopecia Areatamentioning
confidence: 99%